EphA4 is associated with multiple cell types in the marmoset primary visual cortex throughout the lifespan. (11th March 2014) - Goldshmit, Yona; Homman‐Ludiye, Jihane; Bourne, James A.
Abstract Ephs form the largest family of receptor tyrosine kinases. They interact with the membrane‐bound ligands – ephrins – to control crucial aspects of brain development. EphA4 is the most prominent member of the family in terms of versatility and ability to bind most ephrin ligands. EphA4 regulates brain development by modulating neuronal migration and connectivity. In the present study, we address the involvement of EphA4 in patterning the primary visual cortex (V1) of the marmoset monkey by characterizing the cellular expression profile of EphA4 from late embryonic stages to adulthood. We identified continuous expression on neurons in the cortical plate and mature neocortical layers, similar to that described in the mouse, excluding a role for EphA4 in the formation of borders between visual areas in the marmoset neocortex. In addition to neurons, we also report expression of EphA4 on glial populations, including radial glia and astrocytes. In contrast to what is seen in the mouse, EphA4 expression on astrocytes persists in the adult marmoset V1, including around blood vessels and in the white matter. Robust expression by glial populations, which retain neurogenic properties in the postnatal marmoset, indicates that EphA4 may have acquired additional roles during evolution, with important implications for the benefits of EphA4‐blocking therapies following brain injury.